Konsep Self-Healing Perspektif Al-Qur’an dan Psikologi (Studi Atas Surah Al-Muzammil 1-10) - Saila Rahmatika; Abd. Rozaq; ulil Fauziyah (Asy-Syari’ah : Jurnal Hukum Islam, 2023)
This research was conducted to find out the concept of self-healing in surah al-Muzammil verses 1-10 from the point of view of the Koran and psychology. With the focus of the study: 1) What is the concept of self-healing in surah al-Muzammil verses 1-10. and 2) How is the correlation of self-healing in surah al-Muzammil with self-healing in psychology. By using the tahlili method by explaining all the aspects contained in the verses that are interpreted and describing the description of the meaning contained. The data sources used in this study, in terms of interpretation, the author uses commentary books, namely Tafsir Ibnu Katsir by Abu al-Fida'i Isma'il bin Umar bin Katsir, Tafsir Al-Misbah by Quraish Shihab and other commentary books. Meanwhile, in terms of psychology, it refers to books and scientific works from psychology, including the concept of self-healing in psychology entitled Self Healing Is Knowing Your Own Self, by Dr. Diana Rahmasari. Data collection was carried out by studying the interpretation of surah al-Muzammil, analyzing the concept of self-healing in this interpretation contextually and examining the concept to be connected with psychological theory. There are four ways that can be applied as a self-healing method from surah al-Muzammil verses 1 to 10 including; qiyamul lail, read the Koran with tartil, be patient and stay away from unhealthy environments. Abstrak Penelitian ini dilakukan untuk mengetahui konsep self-healing dalam surah al-Muzammil ayat 1-10 yang dilihat dari kacamata al-Qur’an dan psikologi. Dengan fokus kajian: 1) Bagaimana konsep self-healing dalam surah al-Muzammil ayat 1-10. dan 2) Bagaimana korelasi self-healing dalam surah al-Muzammil dengan self-healing dalam ilmu psikologi. Dengan menggunakan metode tahlili dengan cara memparkan segala aspek yang terdapat dalam ayat-ayat yang ditafsirkan dan mendeskripsikan uraian makna yang terkandung. Sumber data yang digunakan dalam penelitian ini, dari segi tafsir penulis menggunakan kitab-kitab tafsir yaitu Tafsir Ibnu Katsir karya Abu al-Fida’i Isma’il bin Umar bin katsir, Tafsir Al-Misbah karya Quraish Shihab dan kitab tafsir lainnya. Sedangkan dari segi psikologi merujuk pada buku dan karya ilmiah dari ilmu psikologi temasuk Konsep self-healing ilmu psikologi yang berjudul Self Healing Is Knowing Your Own Self, karya Dr. Diana Rahmasari. Pengumpulan data dilakukan dengan cara mengkaji penafsiran surah al-Muzammil, analisis konsep self-healing dalam penafsiran tersebut secara kontekstual dan menelaah konsep tersebut untuk dihubungkan dengan teori psikologi. Terdapat empat cara yang dapat diterapkan sebagai metode self-healing (penyembuhan secara mandiri) dari pada surah al-Muzammil ayat 1 sampai 10 diantaranya; qiyamul lail, membaca al-Quran dengan tartil, sabar dan menjauhkan diri dari lingkungan yang tidak sehat.